KETAHANAN BETON TERHADAP SERANGAN ASAM SULFAT DENGAN BAHAN TAMBAH SILICA FUME - hanafi ashad; Andris Amir (Magister Teknik Sipil Pps Universitas Muslim Indonesia, 2022)
This study aims to examine the degree of damage and the effect of concrete quality on sulfuric acid attack with silica fume added to the compressive strength of concrete with a design concrete quality of 25 MPa and 40 MPa, then formulate the relationship between compressive strength of concrete and good age of concrete at normal concrete and concrete with silica fume. The results showed that concrete without using silica fume was very susceptible to attack by sulfuric acid. The use of the mineral additive silica fume is able to minimize weight reduction and reduction in compressive strength of concrete due to attack by sulfuric acid with a usage percentage of between 13% and 15%.